Pengembangan Media Pembelajaran IPA Kelas IV Berbasis Web (Studi Kasus : SDN 02 Sumberejo) - Dinda Melanda; Ade Surahman; Tien Yulianti (Universitas Teknokrat Indonesia, 2023)
During the Covid-19 pandemic, the government took a policy to shut down all educational institutions by implementing online learning (in the network) or commonly called online that utilizes the internet network that can be done anywhere and anytime. With online learning, it is hoped that it can reduce the risk of transmitting the Covid-19 virus, the application used in online learning that is currently used is WhatsApp. However, there are some obstacles in learning online through the application. By utilizing the technology that is currently developing, it can help and facilitate teaching and learning activities and it is also hoped that this learning media will be innovative to attract student enthusiasm so that students do not get bored and do not get bored in learning and can help and facilitate the teaching and learning process. This research uses Multimedia Development Life Cycle as a system development method which consists of several stages, namely concept, design, Material Collecting, Assembly, Testing and Distribution. The test method uses ISO 25010 for functionality testing with test results to 14 respondents who got 91.67% percentage results and proved that the system was Successful according to its function.